2012
DOI: 10.4236/wjv.2012.21002
|View full text |Cite
|
Sign up to set email alerts
|

Modelling Influenza Vaccination Outcomes

Abstract: Modelling response to influenza vaccination can improve our understanding of how proposed factors, older age, past exposure to influenza viruses, and health disorders, used together, affect antibody production after influenza vaccination. Knowledge about this may be important when planning influenza vaccination protocols. This problem will be emphasized especially in the future, when many alternative vaccines and vaccination approaches are likely to be allowed for a routine use. A major difficulty, in modellin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…In regard to chronic diseases, stages of a disease development, co-morbid conditions, or just biochemical subclinical disorders, may all contribute to the differences of the immune response [21]. Understanding of how these multiple factors work together is possible only by using mathematical models and computer-based methods [22,23]. Computer simulations based on using these methods should complement (and precede) observational studies [24].…”
Section: Factors Affecting Immune Response After Influenza Vaccinationmentioning
confidence: 99%
“…In regard to chronic diseases, stages of a disease development, co-morbid conditions, or just biochemical subclinical disorders, may all contribute to the differences of the immune response [21]. Understanding of how these multiple factors work together is possible only by using mathematical models and computer-based methods [22,23]. Computer simulations based on using these methods should complement (and precede) observational studies [24].…”
Section: Factors Affecting Immune Response After Influenza Vaccinationmentioning
confidence: 99%
“…While it is known that malnutrition can impact the immune system by decreasing cellular immunity and resulting in poor resolution of inflammation, its effect on vaccine responses is not as well established [Gupta et al 2010]. Protein malnutrition and impaired glucose metabolism have been associated with low antibody responses to the influenza vaccination in older people, whilst micronutrient deficiency of vitamin E is also associated with poor vaccine response [Hara et al 2005;Trtica-Majnaric et al 2012]. One study reported no significant difference in improvement during hospitalization for an acute exacerbation in patients with COPD who had nutritional supplementation compared with those who did not [Vermeeren et al 2004].…”
Section: Nutritional Statusmentioning
confidence: 99%